Algebra for the description of data in the composite schemes of algorithms - Akulovskiy, V.G. (Інститут програмних систем НАН України, 2015)
The algebra of the data in which frameworks the complex approach to programming is realized at the description of operating structures and structures of the data in composite schemes of algorithms is offered.